Perioperative visual loss with non-ocular surgery: Case report and review of literature - Pandey, Nidhi (Medknow Publications & Media Pvt Ltd, 2014)
Perioperative visual loss (POVL), a rare but devastating complication, has been reported after spine, cardiac, and head-neck surgeries. The various causes include ischemic optic neuropathy, central or branch retinal artery occlusion, and cortical blindness. The contributory factors described are microvascular diseases and intraoperative hemodynamic compromise. However, the exact association of these factors with post-operative blindness has not yet been confirmed. A case of POVL with caesarian section surgery is being presented. The visual loss occurred due to a combined occlusion of central retinal artery and vein. The causes, presentation, and risk factors of POVL after non-ocular surgery are being discussed.